The Ultimate Skull Base Maneuver Does Not Involve Removing Bone: Quantifying the Benefits of the Interfascial Dissection - Effendi, Sabih T.; Momin, Eric N.; Basma, Jaafar; Michael, L Madison; Duckworth, Edward A.M. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Introduction Several adjunctive osteal skull base maneuvers have been proposed to increase surgical exposure of the anterolateral approach. However, one of the easiest methods does not involve bone: the interfascial temporalis muscle dissection.Methods Sequential dissections were performed bilaterally on five fixed silicone-injected cadaver heads. The amount of sphenoid drilling, scalp retraction, and brain retraction was standardized in all specimens. For each approach, surgical angles were measured for four deep targets: the tip of the anterior clinoid process, the internal carotid artery terminus, the origin of the posterior communicating artery, and the anterior communicating artery. Five surgical angles were measured for each target.Results There were increases on the order of 20% in the anteroposterior (AP)-mid, AP–lateral, and mediolateral–anterior angles for all deep targets with interfascial approach versus a myocutaneous flap. An orbitozygomatic osteotomy additionally increased almost all the angles, but incrementally less so.Conclusion An interfascial dissection increases the surgical exposure to a larger degree than additional osteotomies for several surgically relevant working angles. The addition of an orbitozygomatic osteotomy affords a particular benefit for the suprachiasmatic region. Increased adoption of interfascial mobilization or the temporalis muscle—an easily performed and low-risk maneuver—during anterolateral craniotomies may obviate the need for more involved skull base drilling.
Keywords: anterolateral approach; pterional; interfascial; frontotemporal–orbitozygomatic; orbitozygomatic; skull base